In vitro antioxidant and cytotoxic potential of methanolic extracts of selected indigenous medicinal plants - Kauser, Abida; Shah, Syed Muhammad Ali; Iqbal, Naeem; Anjum Murtaza, Mian; Hussain, Iqbal; Irshad, Asma; Nasir, Suhaila; Akram, Muhammad; Munir, Naveed; Riaz, Muhammad (Progress in Nutrition, 2018)
Plants of medicinal importance are the source of various bioactive compounds. These compounds include the antioxidants which play significant role in preventing oxidative stress caused by the reactive oxygen species (ROS). The present research work was conducted to evaluate the methanolic extracts of selected indigenous medicinal plants for their antioxidant activities by different assays as well as their cytotoxic activity. Methanolic extracts of five selected medicinal plants viz T. chebula; E. officinalis, T. natans, M. oleifera, and T. belenica were prepared and tested for their antioxidant and cytotoxic activities. Total Flavonoid content (TFC) was found to be higher in methanolic extract of E. officinalis (43.12±2.45 μg CE/g) followed by T. natans (21.32±1.06 μg CE/g), T. chebula (15.22±0.63 μg CE/g), T. belenica (13.36±0.78 μg CE/g) and M. oleifera (5.21± 0.75 μg CE/g). Among the studied medicinal plants, highest total phenolic contents (TPC) were found in methanolic extract of E. officinalis (475.5±14.3 μg GAE/g) while the lowest content was found in M. oleifera extract (170.9±5.6 μg GAE/g). The studied plants also showed good radical scavenging activity through DPPH assay and reducing potential through FRAP assay. On hemolytic assay, minimal percent hemolysis of washed RBCs was shown by methanolic extract of E. officinalis (5.89±0.78 %) while highest percent hemolysis was observed in washed red cells treated with T. chebula (13.12±1.2 %). Triton X-100 and normal saline were used as positive and negative controls showing 87.3±8.64 % and 0 % hemolysis, respectively. The current study results indicate that the studied medicinal plants posses considerable antioxidant substances responsible for antioxidative and cytoprotective potential.